2013
DOI: 10.1371/journal.pone.0061045
|View full text |Cite
|
Sign up to set email alerts
|

PADI4 and HLA-DRB1 Are Genetic Risks for Radiographic Progression in RA Patients, Independent of ACPA Status: Results from the IORRA Cohort Study

Abstract: IntroductionRheumatoid arthritis (RA) is a systemic, chronic inflammatory disease influenced by both genetic and environmental factors, leading to joint destruction and functional impairment. Recently, a large-scaled GWAS meta-analysis using more than 37,000 Japanese samples were conducted and 13 RA susceptibility loci were identified. However, it is not clear whether these loci have significant impact on joint destruction or not. This is the first study focused on the 13 loci to investigate independent geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…In a study of RA patients in Western India, Prasannavar et al [19] reported that while HLA-DRB1*04 was strongly associated with RA, *03 and *14 appeared to confer a protective effect. Other study has also suggested that some HLA-DRB1 haplotypes may confer a protective effect [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of RA patients in Western India, Prasannavar et al [19] reported that while HLA-DRB1*04 was strongly associated with RA, *03 and *14 appeared to confer a protective effect. Other study has also suggested that some HLA-DRB1 haplotypes may confer a protective effect [62].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA had significantly higher frequencies of HLA-DRB1*04, *0401, *0404, *0405 and *0410 than controls (OR = 2.28-4.19). A study of Japanese patients with RA showed that the number of SE alleles was significantly associated with progressive joint destruction as well as anticitrullinated peptide antibody positivity and younger age of disease onset [62].…”
Section: Discussionmentioning
confidence: 99%
“…PADI4 has been implicated in the pathogenesis, activity and severity of RA (45,48). Recently, investigations on the relationship between PADI4 gene polymorphisms and RA have been extensively performed in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA) alleles, such as HLA-DRB1*01, HLA-DRB1*13, and HLA-DRB1*15, have been reported to be implicated in the pathogenesis of RA (Kurko et al, 2013). Non-HLA genes, such as peptidylarginine deiminase type 4, protein tyrosine phosphatase nonreceptor 22, interleukin-23 receptor, interleukin-1β (IL-1β), macrophage migration inhibitory factor, tumor necrosis factor alpha (TNF-α), and CD40, have also been shown to be involved in the pathogenesis of RA (Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%